Childhood cellular neurothekeoma: diagnostic challenges in a rare benign neoplasm. - Rodríguez-Lechtig, B.; Mejia, S.; Bocanegra, M.F.; Rolon, M.; Motta, A.; Sánchez, B.F. (European Journal of Pediatric Dermatology, 2025)
Neurothekeoma is a rare benign cutaneous tumor, particularly uncommon in pediatric patients. Histologically, it is classified into three variants – myxoid, cellular, and mixed –based on the proportion of myxoid matrix. The cellular variant, more frequently observed in children, is characterized by a dermal proliferation of epithelioid or spindle-shaped cells with little or no myxoid matrix and a distinct immunohistochemical profile. We report the case of a 10-year-old girl diagnosed with cellular neurothekeoma, highlighting the clinical presentation, histopathological and immunohistochemical findings, along with a review of the recent literature.